The minimal effective volume (MEAV 95) for interscalene brachial plexus block for surgical anesthesia under sedation: A prospective observational dose finding study. Issue 1 (1st January 2017) - Choi, Stephen; Wang, Jane J.; Awad, Imad T.; McHardy, Paul; Safa, Ben; McCartney, Colin J.
ABSTRACT: Background : Interscalene brachial plexus (ISB) block is routinely used to provide anesthesia and analgesia for shoulder surgery. Traditional local anesthetic volumes for ISB result in near universal ipsilateral phrenic nerve paresis potentially including oxygenation and ventilation. Aims : The purpose of this study was to determine the lowest minimal effective anesthetic volume in 95% of patients (MEAV 95) of ropivacaine 0.75% for ISB that provides surgical anesthesia for arthroscopic shoulder surgery. Methods : Prospective observational cohort study in patients undergoing arthroscopic shoulder surgery under ISB (C6 level) with sedation. The dose finding protocol used the Narayana rule for up/down sequential allocation to estimate the MEAV 95 of ropivacaine 0.75%. Successful ISB was defined as complete absence of pinprick sensation in the C5 and C6 dermatomes 30 min postblock. Secondary outcomes assessed included ability to complete surgery with propofol sedation, change in slow vital capacity, room air oxygen saturation postblock, block duration, ISB complications, and numeric rating scale for pain immediately after surgery. Results : The study was stopped early due to futility. Among 225 participants approached, 54 consented to participate. The MEAV 95 for ultrasound-guided ISB of ropivacaine 0.75% for shoulder surgery was unable to be accurately estimated. Local anesthetic volumes between 5 and 20 ml did not influence any of the predefined secondary outcomes. Conclusions : The MEAV 95 (at 30 min) of ropivacaine 0.75% for ultrasound-guided ISB exceeds the local anesthetic volumes that consistently produces hemidiaphragmatic impairment. ISB cannot be guaranteed to provide surgical anesthesia at 30 min without the potential for concomitant phrenic nerve block.